Present distribution of the genus Gnathostoma (Nematoda: Gnathostomatidae) in Mexico - Pérez-Álvarez, Yolanda; García-Prieto, Luis; Osorio-Sarabia, David; Lamothe-Argumedo, Rafael; León-Règagnon, Virginia (Zootaxa, 2008)
Three species of the nematode genus Gnathostoma are distributed in Mexico, namely G. binucleatum, G. lamothei, and G. turgidum. The knowledge of their geographic distribution is important because their potential to infect humans causing gnathostomiasis. In this study, we compile all available records in literature, as well as newly collected data in a data base of 238 records, in 82 localities of 14 sates in Mexico. Tabasco, Oaxaca, and Veracruz states show the largest concentration of localities positive to the infection by these nematode species. The number of host species infected with one of the species of Gnathostoma reaches a total of 80 and fish is the most numerous group with 39 parasitized species, distributed in 11 families.